Comparação de diferentes sistemas de abastecimento através de indicadores de perdas - Silva, Marisa Taís de Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
The objective of this work was to evaluate the losses of different water supply services in Brazil through indicators. For this purpose, data from the Sistema Nacional de Informações sobre Saneamento (SNIS), (Information National System on Water and Sewage), based on 2016 results, referring to four operational indicators related to water losses were collected: IN013 (revenue loss index), IN049 (distribution loss index), IN010 (available volume micro-measurement index) and IN051 (connection loss index). The case studied used data of 10 state water and sewage companies in Brazil. In order to obtain these companies’ losses indicators, the average of 10 most populated municipalities indicators were calculated. The results achieved in this research allowed, among other aspects, to identify critical operational sectors, through data comparison process. High values of IN013, IN049 and IN051 indices and low values of IN10 are symptoms of ineffective management, generating negative environmental and economic impacts, as was the case of Northern companies. Analyzing the indicators of the water supply service companies is paramount to evaluate the water and sewage sector, to create managing services tools, to plan and implement public policies, among others.
Monografia
Keywords: Benchmarking; SNIS; Índices de perdas; Benchmarking; SNIS; Loss indices; ENGENHARIAS::ENGENHARIA CIVIL